Pemanfaatan Ex-Bantaran Rel Kereta Api Dan Jembatan Layang Untuk Sarana Publik Yang Kreatif - Zulkifli Siregar; Andri Andri (HEXAGON, 2022)
This research study was conducted in the underpass of the flyover in the corridor of Jalan Ampera Medan. The purpose and objective is to provide a scientific concept related to the arrangement of the space under the flyover which is not currently well managed and tends to cause vandalism in the space. just linearly below it. Utilization of the structural elements of the flyover and its environment can provide attractiveness and be used as a medium of information to convey moral messages through creativity and well-managed works. Thus the space under the flyover which was initially unproductive will turn into an interest point for the surrounding environment. Furthermore, space and area that have been well-organized will certainly give birth to an economic revival through the support of a well-planned and correct management system. The initial material needed for this research is the condition of the existing linear space under the flyover of the Ampera Medan road corridor. Observations to the research location were carried out to determine and map the conditions of land use, the shape of the flyover construction structure that will be used as a point of interest and the potentials of the surrounding environment that can be used as support for creative and innovative public space planning. Primary materials taken from the field will be described into a CAD application so that they become site plan products and base materials. Furthermore, the site plan is also used in the analysis process and relates it to other secondary materials.